A three-fingered, touch-sensitive, metrological micro-robotic assembly tool. (29th October 2015) - Torralba, Marta; Hastings, D J; Thousand, Jeffery D; Nowakowski, Bartosz K; Smith, Stuart T
Abstract: This article describes a metrological, robotic hand to manipulate and measure micrometer size objects. The presented work demonstrates not only assembly operations, but also positioning control and metrology capability. Sample motion is achieved by a commercial positioning stage, which provides XYZ-displacements for assembly of components. A designed and manufactured gripper tool that incorporates 21 degrees-of-freedom for independent alignment of actuators, sensors, and the three fingers of this hand is presented. These fingers can be opened and closed by piezoelectric actuators through levered flexures providing an 80 μ m displacement range measured with calibrated opto-interrupter based, knife-edge sensors. The operational ends of the fingers comprise of a quartz tuning fork with a 7 μ m diameter 3.2 mm long carbon fiber extending from the end of one tuning fork tine. Finger-tip force-sensing is achieved by the monitoring of individual finger resonances typically at around 32 kHz. Experimental results included are focused on probe performance analysis. Pick and place operation using the three fingers is demonstrated with all fingers being continuously oscillated, a capability not possible with the previous single or two finger tweezer type designs. By monitoring electrical feedback during pick and place operations, changes in the response of the three probes demonstrate the ability to identify both grab and release operations. Component metrology has been assessed by contacting different micro-spheres of diameters 50(±7.5) μ m, 135(±20) μ m, and 140(±20) μ m. These were measured by the micro robot to have diameters of 67, 133, and 126 μ m respectively with corresponding deviations of 4.2, 4.9, and 4.3 μ m. This deviation in the measured results was primarily due to the manual, joystick-based, contacting of the fingers, difficulties associated with centering the components to the axis of the hand, and lower contact sensitivity for the smallest sphere. Finally, assemblies of spheres onto the edge of a razor blade plus assembly of spherical contact probes for micro-meter scale coordinate measurement applications are presented.